Binder-free synthesis of metal organic framework derived cobalt sulfide on carbon cloth for efficient energy storage devices. (15th November 2022) - Xiao, Cheng-Yu; Chen, Tzu-Yang; Chung, Ren-Jei; Yougbaré, Sibidou; Lin, Lu-Yin; Wu, Yung-Fu
Abstract: Cobalt based metal organic framework (Co-MOF) derivatives are regarded as attractive electroactive materials for energy storage, due to its high surface area, excellent pore structure and the possible formation of cobalt compounds. Cobalt sulfide with multiple redox states of Co and high electronegativity of S can produce numerous redox reactions for electron storage and provide high electrical conductivity for charge transfer. In this work, it is the first time to synthesize the novel binder-free sulfurized Co-MOF electrode as energy storage electrode of supercapacitor (SC). Three sulfur sources are used to sulfurize the Co-MOF electrode in hydrothermal process. The sulfurized Co-MOF prepared using thiourea (S67/CC-thiourea) shows wrinkles surface and particle connected aggregations, which can provide high surface area and electrical conductivity, respectively. The highest specific capacitance (CF ) of 469.5 F/g at 4 A/g is achieved for the S67/CC-thiourea electrode. The untreated Co-MOF electrode merely shows a CF value of 8.0 F/g. An asymmetric SC is assembled using activated carbon negative electrode and S67/CC-thiourea positive electrode. A maximum energy density of 3.25 Wh/kg at 275 W/kg, and CF retention of 106 % and Coulombic efficiency higher than 91 % after 10, 000 charge/discharges cycles are obtained for the asymmetric SC. This work opens new routes for creating novel MOF derivatives directly on conductive substrate using simple experimental processes. Graphical abstract: Unlabelled Image Highlights: A novel binder-free sulfurized cobalt-based metal organic framework (Co-MOF) is made. Three sulfur sources were used to sulfurize Co-MOF electrode in hydrothermal process. The untreated Co-MOF electrode only shows a capacitance (CF ) of 8.0 F/g at 4 A/g. A CF value of 469.5 F/g at 4 A/g is got for optimal sulfurized Co-MOF electrode. Supercapacitor shows CF retention-106 % and Coulombic efficiency-91 % in 10, 000 time.